The Efektivitas Sediaan Topikal Berbasis Tanaman Herbal terhadap Penyembuhan Luka Sayat pada Studi In Vivo: Sebuah Tinjauan Naratif: Sebuah Tinjauan Studi Hewan Coba - Rijal Rahman Hakim; Syazili Mustofa; Giska Tri Putri; Hendri Busman (Medula, 2026)
Incision wounds are injuries that result in the disruption of skin tissue continuity and are at risk of infection as well as delayed healing if not managed optimally. Standard treatment often uses chemical antiseptics which risk causing irritation and resistance side effects. Indonesia has a wealth of herbal plants that have the potential to be effective wound healing alternatives. To evaluate the effectiveness of herbal-based topical preparations on incision wound healing in in vivo studies of white rats (Rattus norvegicus). This study is a narrative review conducted by searching for experimental scientific articles (True Experimental) published between 2020–2025. Inclusion criteria included in vivo studies on white rats with incision wound models, using herbal topical preparations (gels, ointments, creams), and comparing them with positive controls (standard drugs) and negative controls. Nine selected articles were analyzed descriptively. The review results showed that plants such as Papaya Stem, Jatropha curcas Leaves, Jatropha multifida Leaves, Lantana camara, Stenochlaena palustris, Shallots, Allium chinense, Lime Peel, and Taro showed significant wound healing activity. Topical preparations with optimal extract concentrations were able to match the healing speed of standard drugs and improve histopathological parameters (collagen and fibroblasts). Based on the literature review, herbal-based topical preparations are proven effective in accelerating incision wound healing in rat models and have the potential to be developed as phytopharmaceuticals.